Forecast and prospects of poultry industry development in the period by 2020 - Бойко, Людмила Олександрівна; Бойко, Вікторія Олександрівна; Аверчева, Наталя Олександрівна (Technology audit and production reserves, 2016)
Poultry industry in Ukraine is economically attractive and competitive kind of agribusiness, as evidenced by a steady growth dynamics of poultry meat and eggs. Therefore, the object of our study is the poultry industry in Ukraine and its individual enterprises. Methods of applied system analysis, comparison, modeling, calculation-constructive and others were used during research. Organizational and economic principles of poultry production, which are formed by a system of internal and external factors, are studied in the article. The features of poultry production in Ukraine and Kherson region for the period 2010-2014 are analyzed. Directions to improve economic efficiency and a forecast for poultry production by 2020 are proposed. Evaluation of the effectiveness of the JSC "Chornobaivske" was conducted, ways to optimize costs and increase profitability of the industry in the future were developed. Expediency of further study of factors that affect the efficiency of poultry products is marked. Recommendations for the disposal of waste and the full utilization of poultry with further technical modernization of the enterprise were given. The study found that the production of eggs of birds will increase due to the fact that most enterprises will process their products on egg powder, which has a great demand in the food industry. Data analysis and forecasting the industry by polynomial trend shows a possible fluctuations. This highlights the complexity of recovery in the conditions of competition under both internal and external factors.